Characteristics and outcomes of percutaneous coronary interventions in patients with spontaneous coronary artery dissection. A study from the administrative minimum data set of the Spanish National Health System - Alfonso, Fernando; Fernández-Pérez, Cristina; del Prado, Náyade; García-Guimaraes, Marcos; Bernal, José Luis; Bastante, Teresa; del Val, David; García-Márquez, María; Elola, Javier (Frontiers in Cardiovascular Medicine, 2022)
Background Coronary revascularization in patients with spontaneous coronary artery dissection (SCAD) is challenging. Indications and results of percutaneous coronary interventions (PCI) in SCAD patients are not well established. Aim To assess indications and results of PCI in SCAD. Methods The minimum basic data set of the Spanish National Health System (years 2016−2019) was used to identify 804 episodes of acute myocardial infarction (AMI) and SCAD, with a crude in-hospital mortality rate of 3%. Of these, 368 (46.8%) patients were revascularized with PCI during admission whereas 436 (54.2%) were managed conservatively. Results Revascularization and in-hospital mortality rates both declined over the study period (p for trend both < 0.05). SCAD patients treated with PCI were older, more frequently male, and had higher frequency of diabetes, ST-segment elevation AMI and cardiogenic shock, compared to patients managed conservatively. The crude in-hospital mortality rate was higher in patients treated with PCI (4.9% vs. 1.4%; p = 0.004). However, after adjusting by propensity score (223 pairs) the in-hospital mortality rate was similar in the two groups (Adj OR: 1.21; 95%CI: 0.30−1.57; p = 0.76). Readmissions at 30-days were higher in patients managed conservatively (7.1 vs. 1.6%, p < 0.001) and this difference was maintained after propensity score adjustment (Adj average treatment effect: 2% vs. 12.2%; OR: 0.15; 95%CI: 0.04−0.45; p < 0.001). Conclusion Revascularization is frequently used in unselected patients with AMI and SCAD but its use is declining. Patients with SCAD treated with PCI have a higher in-hospital mortality but this appears to be explained by their adverse baseline clinical characteristics.